Determination Of Online Learning With It Availability As A Moderating Variable - Naylatul Afridah; Sarwenda Bidur; Eny Maryanti (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study aims to examine the effect of hybrid learning implementation, attitudes and acceptance behavior of accounting study study students on online learning with introductory accounting courses supported by the availability of technology carried out during the covid-19 pandemic. This research method uses a quantitative approach with primary data obtained through data collection techniques for distributing questionnaires to a sample of students. The data was tested using the SEMPLS 3.0 application. The results show that the implementation of hybrid learning has an effect on online learning in introductory accounting courses, which is supported by the availability of technology. However, the results of research on the attitudes and behavior of students' acceptance of accounting study programs have no effect on online learning in introductory accounting courses which are supported by the availability of technology.